التكافؤ اللغوي-الثقافي في النّص الهدف المسرحي في الترجمة - إبراهيم, ياسر; هيفا, منال (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This piece of research attempts to explain the two types of translation: Linguistic Translation that focuses on translating the linguistic units, and Communicative Translation that focuses on conveying the message and impressing the reader. There is also an attempt to disclose the importance of achieving equivalence in translation. Besides, some problems that may face the translators of the dramatic text are highlighted and some strategies to avoid TL misrepresentation through pinpointing linguistic and socio-cultural differences proposed. The analysis is supported by examples from the two plays proposed. Every Man and Stick and Bones translated from English into Arabic by two different translators. يأتي هذا البحث كمحاولةٍ لشرح نوعين من أنواع الترجمة وهما الترجمة اللغوية حيث يتم التركيز على ترجمة الوحدات اللغوية، والترجمة التواصلية حيث يتم التركيز على إيصال الرسالة و ترك أثرٍ قويٍ في نفس القارئ. في البحث أيضاً محاولة لكشف أهمية تحقيق التكافؤ في الترجمة. كما يتم تسليط الضوء على بعض المشاكل التي من الممكن أن تواجه مترجمي النصوص المسرحية و تقديم جملةً من الاستراتيجيات بغية تجنب سوء تقديم المقابلات في اللغة الهدف. موضحاً بذلك أوجه الخلاف اللغوية والثقافية التي تؤثر على الترجمة. من جهةٍ أخرى، تمّ دعم هذا التحليل بأمثلةٍ مستقاة من مسرحيتي عصيّ وعظام وكل إنسان اللتين تمت ترجمتهما من اللغة الانكليزية إلى اللغة العربية من قبل مترجمين اثنين.